The End of Finance and Financial Stabilisation - Jan Toporowski (Wirtschaft und Gesellschaft (WuG), 2003)
The financial system that is described in economics textbooks is one that serves as an amenity for industry, commerce, government and households. The prevailing view among economists is the Schumpeterian one that the financial system is essentially a passive supplier of credit to enterprise in other parts of the economy (the real economy), so that financial disturbances merely reflect disequilibrium in the real economy, or are the outcome of inappropriate monetary policies. The author puts toward an alternative hypothesis, in which the inflation of the market for Iong-term securities becomes the animating force of economic boom and crisis. ln this paper he extends this argument by showing how it is different from the view of Marx and much contemporary finance theory. The paper then gives an outline of the theory of capital market inflation, and how it changes the end, or purpose of finance. lt concludes by considering a possible way in which the capital market can be stabilised.
Keywords: 330